Interactive Effects of Nutrient and Mechanical Stresses on Plant Morphology - Puijalon, Sara (Oxford University Press, 2007)
BACKGROUND AND AIMS: Plant species frequently encounter multiple stresses under natural conditions, and the way they cope with these stresses is a major determinant of their ecological breadth. The way mechanical (e.g. wind, current) and resource stresses act simultaneously on plant morphological traits has been poorly addressed, even if both stresses often interact. This paper aims to assess whether hydraulic stress affects plant morphology in the same way at different nutrient levels. METHODS: An examination was made of morphological variations of an aquatic plant species growing under four hydraulic stress (flow velocity) gradients located in four habitats distributed along a nutrient gradient. Morphological traits covering plant size, dry mass allocation, organ water content and foliage architecture were measured. KEY RESULTS: Significant interactive effects of flow velocity and nutrient level were observed for all morphological traits. In particular, increased flow velocity resulted in size reductions under low nutrient conditions, suggesting an adaptive response to flow stress (escape strategy). On the other hand, moderate increases in flow velocity resulted in increased size under high nutrient conditions, possibly related to an inevitable growth response to a higher nutrient supply induced by water renewal at the plant surface. For some traits (e.g. dry mass allocation), a consistent sense of variation as a result of increasing flow velocity was observed, but the amount of variation was either reduced or amplified under nutrient-rich compared with nutrient-poor conditions, depending on the traits considered. CONCLUSIONS: These results suggest that, for a given species, a stress factor may result, in contrasting patterns and hence strategies, depending on a second stress factor. Such results emphasize the relevance of studies on plant responses to multiple stresses for understanding the actual ecological breadth of species.